Punishment, communication, and community - Duff, Antony (Oxford University Press, 2001)
In this book, he offers his fullest account of this theory to date. His approach, if generally adopted, would require a transformation of many of our existing practices of state punishment. This is a deep and challenging volume: no-one who is seriously concerned with the nature of and justification for state punishment can afford to neglect its arguments."--Anthony Bottoms, Institute of Criminology, Cambridge University